Innovations in Fitness Works and Physical Education (Journal of Pedagogical Inventions and Practices, 2022)
This article describes the organization of physical education, sports and fitness classes in secondary schools, the methods of their organization, the purpose and objectives of health activities, its features and the conduct of movement games. We are talking about the methodology